Lost in Transition: The Dark Side of Emerging Adulthood - Adamczyk, Amy (Sociology of religion, 2012)
In Lost in Transition, Smith et al. isolate and analyze the challenges that emerging adults are currently facing. Emerging adulthood refers to the period of development between the ages of 18 and 23 when teens have graduated from high school and are beginning their lives as adults. This is the third book that Smith et al. have written using data collected through the National Study of Youth and Religion (NSYR). Lost in Transition primarily relies on the 230 interviews that were part of the latest wave of the NSYR. The quantitative survey data that the NSYR also collected are only occasionally incorporated., The book is divided into chapters that focus on what Smith et al. see as major concerns for emerging adults.